Update Breast Cancer 2018 (Part 4) – Genomics, Individualized Medicine and Immune Therapies – in the Middle of a New Era: Treatment Strategies for Advanced Breast Cancer - Müller, Volkmar; Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lüftner, Diana; Welslau, Manfred; Belleville, Erik; Brucker, Sara Y.; Schütz, Florian; Fasching, Peter A.; Fehm, Tanja N.; Kolberg, Hans-Christian; Schneeweiss, Andreas; Overkamp, Friedrich (Geburtshilfe und Frauenheilkunde, 2018)
New therapeutic developments aimed at treating women with advanced breast cancer currently focus both on identifying patients eligible for targeted therapeutic concepts and on the continuing development of immune therapies. The data on CDK4/6 inhibitors are now complete and consistent in this class of substances (palbociclib, ribociclib and abemaciclib). Further pathways under investigation are PI3K and AKT signalling pathways along with diverse approaches to their inhibition. Initial study results were also presented recently on both mechanisms of action. Insights into the PARP inhibitors, moreover, are increasing; studies in this respect are also examining in which population they can be used most effectively. This review offers a summary of the recent studies and an outline of the latest developments.Neue Therapieentwicklungen zur Behandlung von Patientinnen mit fortgeschrittenem Mammakarzinom konzentrieren sich zurzeit sowohl auf die Identifikation von Patientinnen für zielgerichtete Therapieansätze als auch auf die Weiterentwicklung von immuntherapeutischen Ansätzen. Die Datenlage zu den CDK4/6-Inhibitoren konnte vervollständigt werden und ist konsistent in dieser Klasse von Substanzen (Palbociclib, Ribociclib und Abemaciclib). Weitere Signalwege, die untersucht werden, sind der PI3K-und der AKT-Signalweg sowie verschiedene Ansatzpunkte zu deren Hemmung. Für beide Wirkmechanismen liegen auch erste Studienergebnisse vor, die vor Kurzem vorgestellt wurden. Außerdem wachsen die Erkenntnisse zu den PARP-Inhibitoren, für die auch untersucht wird, in welcher Population sie am effektivsten eingesetzt werden können. Dieser Review-Artikel soll die aktuellen Studien zusammenfassen und einen Ausblick der neuesten Entwicklungen geben.
Keywords: breast cancer; treatment; metastases; CDK4/6; PD1/PDL1